Exploration Of The Potential Of Phaleria Macrocarpa Against Colon Cancer Using A Network Pharmacology Approach Network Pharmacology-Based Exploration of Phaleria Against Colon Cancer - Laili Khusnul Khotimah; Restia Prasisila Hidayanti Nawangsasih; Diana Magdalena Larassati; Syalzhabilla Yasmin; Adelia NurFitri; Himyatul Hidayah (International Journal of Health Engineering and Technology, 2026)
Colon cancer is one of the leading causes of cancer-related mortality worldwide. Phaleria macrocarpa contains various bioactive secondary metabolites with potential anticancer activity. This study aimed to identify the potential molecular targets of Phaleria macrocarpa against colon cancer using a network pharmacology approach. Compound data were collected from LC-MS/MS-based studies and screened using pkCSM. Protein targets were predicted using SuperPred and compared with colon cancer-related proteins obtained from GeneCards. Protein interaction and network topology analyses were performed using STRING-DB, Cytoscape, and CytoNCA. The results identified 10 overlapping target proteins, namely TLR4, GLS, MAP2K2, LDHA, STAT3, NFKB1, PTGS1, GSK3B, STAT1, and SLC2A1. Network analysis revealed that NFKB1 were the key targets with the highest centrality values. These findings suggest that Phaleria macrocarpa may inhibit colon cancer progression through multiple molecular targets and biological pathways.